2011
DOI: 10.1113/jphysiol.2010.201855
|View full text |Cite
|
Sign up to set email alerts
|

TRPM2: a multifunctional ion channel for calcium signalling

Abstract: The transient potential receptor melastatin-2 (TRPM2) channel has emerged as an important Ca 2+ signalling mechanism in a variety of cells, contributing to cellular functions that include cytokine production, insulin release, cell motility and cell death. Its ability to respond to reactive oxygen species has made TRPM2 a potential therapeutic target for chronic inflammation, neurodegenerative diseases, and oxidative stress-related pathologies. TRPM2 is a non-selective, calcium (Ca 2+ )-permeable cation channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
242
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 248 publications
(250 citation statements)
references
References 109 publications
(348 reference statements)
7
242
0
1
Order By: Relevance
“…A potential link between NAD depletion and T1D was demonstrated by the findings that knockout of PARP in mice prevents streptozotocin (STZ)-induced β-cell death and hyperglycaemia [5,7]. Subsequent studies however have shown that ADP-ribose, the by-product of NAD metabolism, is a potent activator of the transient receptor potential (melastatin) 2 (TRPM2) channel [8] and inhibition of TRPM2 channels prevents apoptosis [9][10][11][12]. These later results raised the possibility that TRPM2 (ADPribose)-mediated β-cell apoptosis could also contribute to T1D, but its role relative to energy depletion has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A potential link between NAD depletion and T1D was demonstrated by the findings that knockout of PARP in mice prevents streptozotocin (STZ)-induced β-cell death and hyperglycaemia [5,7]. Subsequent studies however have shown that ADP-ribose, the by-product of NAD metabolism, is a potent activator of the transient receptor potential (melastatin) 2 (TRPM2) channel [8] and inhibition of TRPM2 channels prevents apoptosis [9][10][11][12]. These later results raised the possibility that TRPM2 (ADPribose)-mediated β-cell apoptosis could also contribute to T1D, but its role relative to energy depletion has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Although H 2 O 2 can directly activate the channel, activation is largely mediated by ADP-ribose [8,[10][11][12]. The channels are also directly activated through the oxidation of a methionine located in the cytoplasmic N-terminal domain [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characters of these two inhibitors probably attribute to the nature of ADPR analogues. It is well known that ADPR gates TRPM2 through binding to the cytosolic C‐terminal NUDT9‐H domain which is a unique structure domain among TRP channels 5. The two inhibitors 7i and 8a likely compete with ADPR for binding to the NUDT9‐H domain, serving as intracellular inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM2, a subtype of TRP‐melastatin subfamily (TRPM), is a multifunctional Ca 2+ permeable and nonselective cation channel 4. It functions as an important Ca 2+ signalling regulator in a variety of cells, contributing to cellular functions including cytokine production, insulin release, cell motility, oxidative stress and cell death 5. TRPM2 is activated by reactive oxygen species (ROS) such as hydrogen peroxide and is considered as a chanzyme containing a unique C‐terminal Nudix hydrolase domain, that is homologous to the ADPR pyrophosphatase nudix hydrolase 9 (NUDT9) 6, 7, 8.…”
Section: Introductionmentioning
confidence: 99%